2019
DOI: 10.3390/ijms20051135
|View full text |Cite
|
Sign up to set email alerts
|

Current Structural Knowledge on the CNNM Family of Magnesium Transport Mediators

Abstract: The cyclin and cystathionine β-synthase (CBS) domain magnesium transport mediators, CNNMs, are key players in maintaining the homeostasis of magnesium in different organs. The human family includes four members, whose impaired activity causes diseases such as Jalili Syndrome or Familial Hypomagnesemia, but is also linked to neuropathologic disorders, altered blood pressure, and infertility. Recent findings demonstrated that CNNMs are associated with the highly oncogenic phosphatases of the regenerating liver t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 81 publications
1
45
0
Order By: Relevance
“…Among the various mechanisms of Mg 2+ sensing and transport, proteins of the Cyclin M (CNNM) family were shown to play an important role in the intracellular sensing of the Mg 2+ availability [4] [5]. The CNNM family has 4 members in mammalians, which are highly conserved but have different tissue distribution [4] [6][3] [5]. CNNM1, CNNM2 and CNNM4 have highest expression levels in brain, kidney and intestine, respectively whereas CNNM3 shows a ubiquitous expression pattern [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various mechanisms of Mg 2+ sensing and transport, proteins of the Cyclin M (CNNM) family were shown to play an important role in the intracellular sensing of the Mg 2+ availability [4] [5]. The CNNM family has 4 members in mammalians, which are highly conserved but have different tissue distribution [4] [6][3] [5]. CNNM1, CNNM2 and CNNM4 have highest expression levels in brain, kidney and intestine, respectively whereas CNNM3 shows a ubiquitous expression pattern [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the human family study, deficiency of CNNM2 has been identified in patients suffering from intellectual disability, seizures, hypomagnesemia, infertility, and altered blood pressure ( 39 ). Arjona et al reported the role of cnnm2 gene isoforms in zebrafish using a morpholino knockdown model that caused disturbed brain development, increased embryonic spontaneous contractions, weak touch-evoked escape behavior, and reduced magnesium content, indicating an impairment of renal Mg 2+ absorption ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, more than 600 enzymatic reactions involving magnesium have been discovered [ 14 ]. About 99% of total body magnesium is distributed between different tissues in humans, amounting to approximately 25 g of magnesium in total for adults, with the largest proportion found in bones [ 15 ]; only 1–2% of the total magnesium is located in the blood. Mg 2+ can act as an antagonist to reduce Ca 2+ signaling in endothelium [ 16 ].…”
Section: Magnesiummentioning
confidence: 99%